Highly active and coke resistant Ni/SiO2 catalysts for oxidative reforming of model biogas: Effect of low ceria loading. (May 2017) - Kathiraser, Y.; Wang, Z.; Ang, M.L.; Mo, L.; Li, Z.; Oemar, U.; Kawi, S.
Abstract: Biogas (consisting of greenhouse gases; CO2 and CH4 ) is a potential renewable resource for valuable syngas production. This is an industrially important method to utilize CO2 for high value chemical/energy production. Stability of economically viable Ni based catalysts is crucial to increase industrial viability of this environmentally sustainable process. Highly active and coke resistant ceria-promoted Ni/SiO2 catalysts were prepared using in-situ self-assembled core shell precursor route. Low ceria loading (0.5 wt%) was found beneficial in promoting the oxidative reforming of biogas activity as well as minimizing carbon deposition at the conditions tested. The positive influence exerted by such low loading of ceria was attributed to anchorage of ceria at interfacial sites of the Ni/SiO2 support, promoting intimate interaction of Ni–SiO2 within the mesopore wall via formation of nickel silicates with strong metal-support interaction. Such low loading of ceria, weakened the catalyst' Lewis acidity, and supplied oxygen vacancies which are crucial to maintain the reducibility of Ni, ensuring high activity and stability.